Association Between Motor Competence, Physical Fitness, and Academic Achievement in Physical Education in 13- to 16-Year-Old School Children - Vist Hagen, Ruben; Lorås, Håvard; Sigmundsson, Hermundur; Haga, Monika (Frontiers in Sports and Active Living, 2022)
Due to accommodating Reviewer`s comments in the abstract section we have exceeded the word limit. Please see article-file (word and pdf) for complete abstract, and please let us know if this needs to be addressed further.